Examining the impact of the attractiveness of alternatives on customers' perceptions of price tolerance: Moderation and mediation analyses. Issue 4 (December 2016) - Temerak, Mohamed Sobhy
Abstract The current literature provides mixed support for the positive influence of competitors on customers' perceptions of price tolerance (Herrmannet al, Psychology & Marketing, 200421 (7), 533–551). This paper examines a number of mediators and moderators of this relationship, such as positive switching barriers, negative switching barriers and customer satisfaction. A total of 162 valid responses was collected from the financial brokerage context by means of a random sample. The data were analysed using the Partial-least square (PLS) approach to structural equation modelling. The findings show that customers' satisfaction with the service provider partially mediates the positive effect of alternatives on price tolerance. Negative, not positive, switching barriers were found to weaken the effect on price tolerance of the attractiveness of alternatives.